How Xenon Works: Neuro and Cardioprotection Mechanisms - Morais, Ricardo (2014)
Introduction: The Xenon, a noble gas, has anesthetics properties, associated with remarkable hemodynamic stability as well as cardioprotective, neuroprotective proprieties. Its physicochemical characteristics give him a quick induction and emergence of anesthesia, being free of deleterious effects in all organs and showing no teratogenicity. Such properties have led to a growing interest in improving the knowledge about this noble gas, in order to assess the mechanisms of neuro and cardioprotection induced and to assess the clinical indications for its use.Material and Methods: Qualitative review of clinical trials on anesthesia with xenon. Studies were identified from MEDLINE and by hand-searching, using the following keywords: xenon, xenon anestesia, xenon neuroprotection, xenon cradioprotection.Results: After several studies, including two randomized multicenter controlled trials, the use of xenon as an anesthetic in patients ASA I-II was approved in March 2007. However his use in clinical practice has been strongly limited by it´s high price. It seems unlikely that the advantages it offers in relation to other anesthetics justify it´s use in patients ASA I-II. Although, xenon may be a valuable asset in the reduction of co-morbilities and mortality in anesthesia of patients ASA III-IV, unfortunately, there are no large randomized control studies to prove it.Discussion: Unfortunately, there are still no randomized or multicentric studies showing a favourable cost-benefit profile of xenon in ASA III-IV patients vs. other anaesthetics.Conclusion: The usefulness of xenon in Anesthesiology requires more studies to be defined.